Lithium ion battery

By using additives with specific structures in the electrolyte of lithium iron phosphate batteries, the problems of poor high-temperature cycling and poor storage performance of the battery are solved, and better high-temperature performance and lower impedance are achieved.

CN119764567AActive Publication Date: 2025-04-04CALB GROUP CO LTD

Patent Information

Application Number
CN202411952747.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Lithium iron phosphate/graphite lithium ion batteries have problems of poor high-temperature cycling and poor storage performance. Although the use of vinyl carbonate (VC) as an additive in the prior art has a certain improvement effect, excessive VC content will lead to excessive impedance and limited improvements to high-temperature cycling.

Method used

The additives with specific structures are used in combination, including the alkoxycarbonyl isothiocyanate compound of the structure represented by formula (I) and the alkenyl alkyl trisilazane compound of the structure represented by formula (II). These additives inhibit interfacial side reactions and improve the high-temperature performance of the battery.

Benefits of technology

Compared with VC, the SEI membrane structure of the additive is denser, and the effect of inhibiting interface side reactions is stronger, which significantly improves the high-temperature cycling performance of lithium iron phosphate batteries while maintaining a low impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764567A_ABST
    Figure CN119764567A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery. The lithium ion battery comprises a positive pole piece and an electrolyte, the positive pole piece comprises a positive active material lithium iron phosphate; the electrolyte comprises an additive a and an additive b, the additive a comprises vinylene carbonate; the additive b comprises a compound with a structure as shown in a formula (I) and a compound with a structure as shown in a formula (II). Two additives are used in cooperation, VC is partially replaced, the addition amount of VC is reduced, and compared with SEI formed by VC reduction, SEI structures formed by the compound with the structure shown in the formula (I) and the compound with the structure shown in the formula (II) are more compact, the effect of inhibiting interface side reactions is stronger, and the effect of improving high-temperature circulation is better compared with VC. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium iron phosphate battery electrolyte additives, and relates to a lithium ion battery, in particular to a lithium ion battery, and the application of an additive in a lithium ion battery electrolyte to reducing the amount of vinylene carbonate in the electrolyte. Background Art

[0002] Lithium iron phosphate battery is a lithium-ion battery that uses lithium iron phosphate (LiFePO4) as the positive electrode material. Lithium iron phosphate battery has a series of unique advantages such as high operating voltage, high energy density, long cycle life, low self-discharge rate, no memory effect, green environmental protection, etc., and supports stepless expansion, suitable for large-scale electric energy storage, and has good application prospects in the fields of safe grid connection of renewable energy power stations, grid peak regulation, distributed power stations, UPS power supplies, emergency power supply systems, etc. Especially with the vigorous development of the electric vehicle industry in recent years, lithium iron phosphate batteries occupy an important share in the industry in actual commercial applications. And with the continuous development of downstream application industries, higher requirements are also put forward for lithium iron phosphate batteries.

[0003] Lithium iron phosphate / graphite lithium-ion batteries have always had problems with poor high-temperature cycling and storage performance. Although adding the additive vinylene carbonate (VC) to the electrolyte can improve the problem, VC wraps the negative electrode graphite to avoid side reactions between the negative electrode main material and the electrolyte and improves the cycle, but VC's improvement on high-temperature cycling is limited and still cannot meet the requirements.

[0004] Therefore, how to find a more appropriate way to solve the above-mentioned technical problems of existing lithium iron phosphate batteries has become one of the urgent problems to be solved by many front-line researchers and scientific research enterprises in this field. Summary of the invention

[0005] In view of this, the present invention provides a lithium ion battery and an application of an additive in a lithium ion battery electrolyte to reduce the amount of vinylene carbonate in the electrolyte. The present invention adopts a combined application of additives with a specific structure, which has a stronger effect of inhibiting interfacial side reactions and a better effect of improving high temperature cycles than vinylene carbonate (VC).

[0006] The present invention provides a lithium ion battery, which comprises a positive electrode sheet and an electrolyte;

[0007] The positive electrode plate includes positive electrode active material lithium iron phosphate;

[0008] The electrolyte includes additive a and additive b;

[0009] The additive a includes vinylene carbonate;

[0010] The additive b includes a compound having a structure represented by formula (I) and a compound having a structure represented by formula (II);

[0011]

[0012] Wherein, in formula (I), M is selected from fluorinated or non-fluorinated C1-C4 alkyl;

[0013] In formula (II), R1, R2, and R3 are each independently selected from H or -C n H 2n+1 , where n≤4;

[0014] R4, R5, and R6 are each independently selected from vinyl, allyl, oxyethylene, or oxyallyl;

[0015] R7, R8, and R9 are each independently selected from hydrogen, methyl or ethyl.

[0016] The present invention provides a lithium-ion battery. Compared with the prior art, the present invention believes that the high-temperature cycle performance of lithium iron phosphate batteries is poor. Although the addition of VC additives to the electrolyte can improve the high-temperature cycle and storage performance, the effect of VC on the improvement of high-temperature cycle performance is limited, and too high a VC content will cause excessive impedance. Therefore, the VC content cannot be too high. Based on this, the present invention specially designs two additives with specific structures to be used in the electrolyte of lithium iron phosphate batteries, thereby further improving the high-temperature performance of lithium iron phosphate batteries. Among them, the additive with the structure shown in formula (I) can improve the high-temperature performance. After addition, the amount of VC can be reduced, ensuring high-temperature performance while ensuring lower impedance; and the additive with the structure shown in formula (II) has better high-temperature performance than VC. Adding a small amount of the additive with the structure shown in formula (II) to match VC can also reduce the amount of VC and obtain more excellent high-temperature performance.

[0017] The electrolyte of the lithium iron phosphate battery provided by the present invention contains an alkoxycarbonyl isothiocyanate compound of the structure shown in formula (I) and an alkenyl alkyl trisilazane compound of the structure shown in formula (II). The compound of the structure shown in formula (I) is reduced at the negative electrode to generate polythioamide, which is resistant to high temperature, and the generated SEI film is stable and has low impedance. Under the premise of improving the power of the lithium iron phosphate battery, the high-temperature cycle and storage performance of the battery are guaranteed; and the compound of the structure shown in formula (II) can undergo polymerization and ring-opening reaction at the negative electrode.

[0018] The generated SEI has a good electronic passivation effect on the interface, reduces the interface side reaction on the negative electrode side, and improves the high temperature cycle and storage performance of the battery. The present invention uses two additives in combination to partially replace VC and reduce the amount of VC added. Moreover, compared with the SEI formed by VC reduction, the SEI structure formed by the compound of the structure shown in formula (I) and the compound of the structure shown in formula (II) is more compact and has a stronger effect of inhibiting the interface side reaction. Therefore, compared with VC, the effect of improving the high temperature cycle is better. DETAILED DESCRIPTION

[0019] In order to further understand the present invention, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0021] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials of conventional purity in the field of lithium-ion battery electrolytes.

[0022] The present invention provides a lithium ion battery, which comprises a positive electrode sheet and an electrolyte;

[0023] The positive electrode plate includes a positive electrode active material, lithium iron phosphate (LiFePO4);

[0024] The electrolyte includes additive a and additive b;

[0025] The additive a includes vinylene carbonate;

[0026] The additive b includes a compound having a structure represented by formula (I) and a compound having a structure represented by formula (II);

[0027]

[0028] Wherein, in formula (I), M is selected from fluorinated or non-fluorinated C1-C4 alkyl;

[0029] In formula (II), R1, R2, and R3 are each independently selected from H or -C n H 2n+1 , where n≤4;

[0030] R4, R5, and R6 are each independently selected from vinyl, allyl, oxyethylene, or oxyallyl;

[0031] R7, R8, and R9 are each independently selected from hydrogen, methyl or ethyl.

[0032] In the present invention, M is selected from fluorinated or non-fluorinated C1-C4 alkyl, or M is selected from fluorinated or non-fluorinated C2-C3 alkyl. Specifically, M can be fluoromethyl, fluoroethyl, fluoropropyl, fluorobutyl, methyl, ethyl, propyl or butyl.

[0033] In the present invention, in formula (II), n≤4, n≤3, or n≤2. Specifically, n may be 1, 2, 3 or 4.

[0034] The present invention adopts an alkoxycarbonyl isothiocyanate compound of the structure shown in formula (I) and an alkenyl alkyl trisilazane compound of the structure shown in formula (II). The compound of the structure shown in formula (I) is reduced at the negative electrode to generate polythioamide, which is resistant to high temperature, and the generated SEI film is stable and has low impedance. Under the premise of improving the power of lithium iron phosphate battery, the high temperature cycle and storage performance of the battery are guaranteed; and the compound of the structure shown in formula (II) can undergo polymerization and ring-opening reaction at the negative electrode, and the generated SEI has a good electronic passivation effect on the interface, reduces the interface side reaction on the negative electrode side, and improves the high temperature cycle and storage performance of the battery. The present invention adopts two additives to partially replace VC and reduce the amount of VC added. Moreover, compared with the SEI formed by VC reduction, the SEI structure formed by the compound of the structure shown in formula (I) and the compound of the structure shown in formula (II) is more compact, and the effect of inhibiting the interface side reaction is stronger, so the effect of improving the high temperature cycle is better than VC.

[0035] In the present invention, the compound of the structure represented by formula (I) preferably includes at least one of the compounds of the structures represented by formulas (I1) to (I17):

[0036]

[0037]

[0038] Furthermore, the compound with the structure represented by formula (I) is preferably ethoxycarbonyl isothiocyanate, that is, the compound with the structure represented by formula (I5).

[0039] The chemical of the structural formula (I) of the present invention preferably adopts the compound of the structure shown in formula (I5), and the battery has better cycle performance and storage performance.

[0040] In the present invention, the compound of the structure represented by formula (II) preferably includes at least one of the compounds of the structures represented by formulas (II1) to (II16):

[0041]

[0042]

[0043] Furthermore, the compound with the structure represented by formula (II) is preferably trivinyltrimethylcyclotrisilazane, that is, the compound with the structure represented by formula (II13).

[0044] The chemical of the structural formula (II) of the present invention preferably adopts the compound of the structure shown in formula (I5), and the battery has better high-temperature performance.

[0045] The high-temperature cycle performance of lithium iron phosphate batteries is poor. Adding the additive VC to the electrolyte can improve the high-temperature cycle and storage performance. However, if the VC content is too high, it will cause excessive impedance. Therefore, the VC content cannot be too high. Additives of formula (I), such as ethoxycarbonyl isothiocyanate, can improve the high-temperature performance. After addition, the amount of VC can be reduced to ensure high-temperature performance while ensuring lower impedance. The additive trivinyltrimethylcyclotrisilazane has better high-temperature performance than VC. Adding a small amount of additives of formula (II), such as trivinyltrimethylcyclotrisilazane, to match VC can also reduce the amount of VC and obtain more excellent high-temperature performance.

[0046] In the present invention, the mass content of the compound of the structure represented by formula (I) in the electrolyte is preferably 0.1% to 2.5%, more preferably 0.5% to 2.2%. In the present invention, if the mass content of the compound of the structure represented by formula (I) is too low, a stable SEI film cannot be formed at the negative electrode; if it is too high, there will be a gas generation problem, resulting in swelling of the battery.

[0047] In the present invention, the mass content of the compound of the structure represented by formula (II) in the electrolyte is preferably 0.1% to 0.6%, more preferably 0.2% to 0.5%. In the present invention, if the mass content of the compound of the structure represented by formula (II) is too low, a stable SEI film cannot be formed at the negative electrode, and if it is too high, the impedance will increase.

[0048] In the present invention, the additive substance of formula (I) is reduced at the negative electrode to generate polythioamide with many ion pathways and low interface impedance, and the SEI film formed by it is stable, which can not only improve the kinetic performance of the lithium iron phosphate battery, but also ensure the high-temperature cycle and storage performance of the battery. However, if the additive substance of formula (I) is added in excessive amount, the gas production will increase; the additive substance of formula (II) undergoes polymerization and ring-opening reaction at the negative electrode, and the generated SEI has a good electronic passivation effect on the interface, but has few ion conduction pathways and high interface impedance, that is, the additive of formula (II) will deteriorate the kinetic performance of the battery while improving the high-temperature cycle and storage performance of the battery.

[0049] Therefore, the present invention further specifically defines the relationship between the content b1 of the additive substance of formula (I) and the content b2 of the additive substance of formula (II).

[0050] In the present invention, the mass content of the additive b in the electrolyte is preferably 0.1% to 3%, that is, the mass percentage of the compound with the structure shown in formula (I) is recorded as b1%, and the mass percentage of the compound with the structure shown in formula (II) is recorded as b2%, b=b1+b2, 0.1≤b1+b2≤3.0, and more preferably 0.5-2.5.

[0051] In the present invention, the mass ratio of the compound represented by the structure of formula (I) to the compound represented by the structure of formula (II) is preferably (1-15):1, that is, 1≤b1 / b2≤15. More preferably, it is (3-13):1.

[0052] In the present invention, the mass content of vinylene carbonate in the electrolyte is preferably 0.5% to 2.5%, more preferably 0.5% to 2.0%. In the present invention, if the mass content of vinylene carbonate is too low, the negative electrode side reaction increases; if it is too high, the negative electrode coating effect is too good and the impedance is large.

[0053] In the present invention, the mass ratio of the total mass of the compound represented by the structure of formula (I) and the compound represented by the structure of formula (II) to the mass ratio of vinylene carbonate is preferably (0.2-2):1, more preferably (0.5-1.8):1. The present invention maintains the total mass of the compound represented by the structure of formula (I) and the compound represented by the structure of formula (II) and the mass ratio of VC within the above range, so that the high temperature performance of the battery is better and the impedance is lower.

[0054] In the present invention, the mass ratio of the vinylene carbonate to the compound of the structure represented by the formula (I) is preferably (0.5-5): 1. The present invention keeps it within the above range, and the battery has higher high temperature performance, lower impedance, and less gas generation.

[0055] In the present invention, the mass ratio of the vinylene carbonate to the compound of the structure represented by the formula (II) is preferably (2-10): 1. The present invention keeps it within the above range, and the high temperature performance of the battery is better without causing greater impedance.

[0056] In the present invention, the positive electrode plate preferably includes a current collector and a positive electrode material coating composited on the current collector.

[0057] In lithium-ion batteries, cohesion reflects the binding force between the particles of the positive electrode active material. Under appropriate cohesion, the positive electrode sheet has good structural stability, which helps to reduce the risk of iron dissolution in the positive electrode material during the battery charging and discharging process due to weak binding force between the particles of the positive electrode active material, exposure of the positive electrode active particles, and increased electrolyte side reactions. When iron dissolution increases, the dissolved iron ions will shuttle to the negative electrode and precipitate on the surface of the negative electrode, causing loss of active lithium and reducing the battery cycle life; at the same time, the iron deposited on the negative electrode exists in the form of a single substance, which will serve as an active center, making the electrolyte easier to reduce, increasing the side reactions of the negative electrode and the electrolyte, and reducing the high-temperature cycle performance of the battery.

[0058] The present invention comprehensively considers the relationship among the cohesion of the positive electrode sheet, the VC content, and the content of the additive b; the iron dissolution of lithium iron increases at high temperature and reaches the negative electrode, causing an increase in the side reaction between the negative electrode and the electrolyte; by increasing the cohesion of the positive electrode sheet, the sheet material is less likely to break, the exposed material active area is smaller, the iron dissolution is less, the side reaction between the electrolyte and the material is less, and the VC dosage and the content of the additive b can be reduced; when the cohesion of the positive electrode sheet is relatively small, the risk of iron dissolution increases, and the sum of the VC content and the additive b content must be increased, so the m×(a+b) value must be maintained within a certain range to ensure the high temperature cycle performance of the battery.

[0059] In the present invention, the cohesion of the positive electrode sheet, vinylene carbonate, the compound of the structure shown in formula (I) and the compound of the structure shown in formula (II) preferably satisfy the following relationship:

[0060] 50≤m×(a+b)≤600 (1);

[0061] Wherein, m is the cohesive force of the positive electrode sheet, in N / m; a% is the mass percentage of vinylene carbonate in the electrolyte, and b% is the sum of the mass percentages of the compound of the structure represented by formula (I) and the compound of the structure represented by formula (II) in the electrolyte.

[0062] Specifically, m×(a+b) may be 100-500, or 200-400.

[0063] In the present invention, the cohesive force of the positive electrode sheet preferably satisfies: 20≤m≤200, more preferably 50≤m≤180, and more preferably 70≤m≤150. The present invention controls the cohesive force within a suitable range, so that the positive electrode sheet has better structural stability, and the positive electrode material particles are not easily exposed. At the same time, it also avoids the need for special design of the positive electrode sheet in order to make the cohesive force higher, such as adding more binder, which causes the proportion of active materials in the battery capacity to be reduced, which is not conducive to the capacity.

[0064] In the present invention, the mass percentage of the vinylene carbonate in the electrolyte, the mass percentage of the compound with the structure represented by formula (I) and the mass percentage of the compound with the structure represented by formula (II) in the electrolyte preferably satisfy: 0.1≤a+b≤5, more preferably 0.5≤a+b≤4.5, more preferably 1.0≤a+b≤4.0, more preferably 1.5≤a+b≤3.5, more preferably 2.0≤a+b≤3.0.

[0065] In the present invention, when the cohesive force m of the positive electrode sheet is ≤60, preferably b / a≥2.5.

[0066] In the present invention, when the cohesion of the positive electrode sheet is less than a certain value, the risk of iron dissolution increases, and additive b improves the high-temperature cyclability of the battery better than VC. Therefore, when the cohesion of the positive electrode sheet is smaller, the high-temperature cyclability of the battery can be better improved by controlling the sum of the VC content and the additive b content within the above range.

[0067] In the present invention, there is no limitation on the method for adjusting the cohesive force of the positive electrode sheet. Specifically, it can be adjusted by the amount and type of the binder.

[0068] In the present invention, the lithium ion battery preferably includes a negative electrode.

[0069] In the present invention, the negative electrode preferably includes a negative electrode active material. Specifically, the negative electrode active material preferably includes graphite and / or silicon-based materials.

[0070] The present invention provides the use of a compound with a structure represented by formula (I) and a compound with a structure represented by formula (II) as an additive in a lithium ion battery electrolyte for reducing the amount of vinylene carbonate in the electrolyte.

[0071] The lithium ion battery provided by the present invention comprises a positive electrode plate, wherein the active material layer of the positive electrode plate comprises lithium iron phosphate, an electrolyte additive comprises VC (vinyl carbonate), wherein the mass percentage content thereof is a%, and an additive X is further included, wherein the additive X is selected from one or more of substance A (Formula I) and substance B (Formula II) (wherein the mass percentage content of substance A is recorded as b1%, and the mass percentage content of substance B is recorded as b2%), wherein M is selected from a fluorinated or non-fluorinated alkyl group having a carbon number of less than or equal to 4, such as a fluorinated methyl group, a fluorinated ethyl group, a fluorinated propyl group, a fluorinated butyl group, a methyl group, an ethyl group, a propyl group, and a butyl group; and R1, R2, and R3 are independently selected from H or -C n H 2n+1 , wherein n≤4, R4, R5, R6 are independently selected from vinyl, allyl, oxyethylene or oxyallyl, and R7, R8, R9 are independently selected from H, methyl or ethyl;

[0072]

[0073] In the present invention, the application preferably includes the application of the compound with the structure represented by formula (I) to improve the high temperature performance and / or storage performance of lithium-ion batteries, and more preferably the application of the compound with the structure represented by formula (I) to improve the high temperature performance and storage performance of lithium-ion batteries.

[0074] In the present invention, the application preferably includes the application of the compound with the structure represented by formula (II) to improve the high temperature performance and / or storage performance of lithium-ion batteries, and more preferably the application of the compound with the structure represented by formula (II) to improve the high temperature performance and storage performance of lithium-ion batteries.

[0075] The above content of the present invention provides a lithium ion battery and an application of additives in lithium ion battery electrolytes to reduce the amount of vinylene carbonate in the electrolyte. The two additives with specific structures specially designed by the present invention are used in combination in the electrolyte of lithium iron phosphate batteries, thereby further improving the high temperature performance of lithium iron phosphate batteries. Among them, the additive with the structure shown in formula (I) can improve the high temperature performance. After addition, the amount of VC can be reduced, ensuring high temperature performance while ensuring lower impedance; and the additive with the structure shown in formula (II) has better high temperature performance than VC. Adding a small amount of trivinyltrimethylcyclotrisilazane to match VC can also reduce the amount of VC and obtain more excellent high temperature performance.

[0076] The electrolyte of the lithium iron phosphate battery provided by the present invention contains an alkoxycarbonyl isothiocyanate compound of the structure shown in formula (I) and an alkenyl alkyl trisilazane compound of the structure shown in formula (II). The compound of the structure shown in formula (I) is reduced at the negative electrode to generate polythioamide, which is resistant to high temperature, and the generated SEI film is stable and has low impedance. Under the premise of improving the power of the lithium iron phosphate battery, the high temperature cycle and storage performance of the battery are guaranteed; and the compound of the structure shown in formula (II) can undergo polymerization and ring-opening reaction at the negative electrode, and the generated SEI has a good electronic passivation effect on the interface, reduces the interface side reaction on the negative electrode side, and improves the high temperature cycle and storage performance of the battery. The present invention adopts two additives to partially replace VC and reduce the amount of VC added. Moreover, compared with the SEI formed by VC reduction, the SEI structure formed by the compound of the structure shown in formula (I) and the compound of the structure shown in formula (II) is more compact, and the effect of inhibiting the interface side reaction is stronger, so the effect of improving the high temperature cycle is better than VC.

[0077] Furthermore, the present invention also comprehensively considers the relationship between the cohesion of the positive electrode plate, the VC content, and the additive content; the iron dissolution of lithium iron increases at high temperature and reaches the negative electrode, causing an increase in the side reaction between the negative electrode and the electrolyte. By increasing the cohesion of the positive electrode plate, the plate material is less likely to break, the exposed material active area is smaller, the iron dissolution is less, and the side reaction between the electrolyte and the material is less, which can better reduce the VC dosage and the additive content; when the cohesion of the positive electrode plate is relatively small, the risk of iron dissolution increases, and the sum of the VC content and the additive b content must be increased, so the cohesion × (VC content + additive content) must be maintained within a certain range, thereby better ensuring the high temperature cycle performance of the lithium iron phosphate battery.

[0078] In order to further illustrate the present invention, a lithium ion battery provided by the present invention and the application of an additive in a lithium ion battery electrolyte in reducing the amount of vinylene carbonate in the electrolyte are described in detail below in conjunction with embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following embodiments.

[0079] The present invention does not limit the method for detecting the cohesive force. Those skilled in the art can detect the cohesive force of the positive electrode sheet according to conventional technical means. For example, the following method can be used for detection:

[0080] The battery was discharged at 0.33C with a cut-off voltage of 2.5V. The positive electrode was taken out of the battery and soaked in dimethyl carbonate (DMC) for 2h and dried at 80℃.

[0081] Take a standard steel plate (50mmx125mm) as the rigidity test base plate, and wipe the surface of the steel plate clean with dust-free paper dipped in alcohol. Stick one side of the 50mmx125mm 3M double-sided tape on the steel plate to ensure smooth pasting and no wrinkles; cut the positive electrode with active coating into 50mmx125mm test samples; paste the electrode to be tested on the other adhesive surface of the double-sided tape, and then paste another layer of double-sided tape on the surface of the electrode. During the pasting process, ensure that the contact is smooth and wrinkle-free. After rolling with a roller, use the universal testing machine to clamp the steel plate at one end of the tensile clamp and the 3M tape at the other end. Set the tensile machine stroke to 100mm, and perform the tensile test at a speed of 300mm / min. Set the tensile machine stroke to 100m, record the curve in the tensile machine software diagram and stop the machine when the displacement is greater than 80mm. Read the average tensile force value of the flat part of the curve as the cohesive force.

[0082] Test method for VC content and additive (Formula 1 and / or Formula 2) content:

[0083] Use battery charging and discharging equipment to discharge the battery. Discharging conditions: current 0.3C, cut-off voltage 2.5V. After recording the battery number / barcode, disassemble the battery in a glove box (H2O≤0.1ppm, O2≤0.1ppm) to collect the electrolyte. There are two ways to collect the electrolyte: After removing the battery cover, ① if there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube and seal it with sealing glue to prevent electrolyte leakage. ② If there is no free electrolyte, use a hydraulic press (Beijing Hengaode Technology Co., Ltd. FY-30 hydraulic press) to continuously pressurize until free electrolyte appears, collect the electrolyte into the sample tube and seal it. ③ Add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer, transfer it to an ultrasonic oscillator and oscillate it for 12 hours to allow the electrolyte in the electrode to be fully mixed with dichloromethane. Then, use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube, and seal the sample tube with sealing glue; inject the collected electrolyte sample into an Agilent Intuvo9000 gas chromatograph-mass spectrometer with a microinjector for testing to obtain a GC-MS spectrum; configure VC, formula I1-I17, and formula II1-II16 into EMC solutions of different concentrations, and inject them into the Agilent Intuvo 9000 gas chromatograph-mass spectrometer respectively to obtain a GC-MS spectrum of the standard substance. The GC-MS spectrum of the electrolyte to be tested is compared with the GC-MS spectrum of the standard to determine whether the electrolyte to be tested contains VC, formula I1-I17, and formula III-II16 (for example, if a peak appears in the spectrum of the electrolyte to be tested at the position where VC is located in the standard spectrum, it is determined that the electrolyte to be tested contains VC, and the same applies to other components). Then, the content of each component in the electrolyte to be tested is determined based on the peak area of ​​each component.

[0084] Example 1

[0085] The battery was prepared and tested according to the following process steps:

[0086] (1) Preparation of positive electrode sheet

[0087] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0088] (2) Preparation of negative electrode sheet

[0089] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0090] (3) Preparation of electrolyte

[0091] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 (ethoxycarbonyl isothiocyanate) and additive b2 (trivinyltrimethylcyclotrisilazane) are added and mixed thoroughly.

[0092] (4) Preparation of isolation membrane

[0093] A polyethylene film is selected as the separating film.

[0094] (5) Preparation of lithium-ion batteries

[0095] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0096] Example 2

[0097] The battery was prepared and tested according to the following process steps:

[0098] (1) Preparation of positive electrode sheet

[0099] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0100] (2) Preparation of negative electrode sheet

[0101] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0102] (3) Preparation of electrolyte

[0103] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0104] (4) Preparation of isolation membrane

[0105] A polyethylene film is selected as the separating film.

[0106] (5) Preparation of lithium-ion batteries

[0107] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0108] Example 3

[0109] The battery was prepared and tested according to the following process steps:

[0110] (1) Preparation of positive electrode sheet

[0111] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0112] (2) Preparation of negative electrode sheet

[0113] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0114] (3) Preparation of electrolyte

[0115] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0116] (4) Preparation of isolation membrane

[0117] A polyethylene film is selected as the separating film.

[0118] (5) Preparation of lithium-ion batteries

[0119] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0120] Example 4

[0121] The battery was prepared and tested according to the following process steps:

[0122] (1) Preparation of positive electrode sheet

[0123] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0124] (2) Preparation of negative electrode sheet

[0125] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0126] (3) Preparation of electrolyte

[0127] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0128] (4) Preparation of isolation membrane

[0129] A polyethylene film is selected as the separating film.

[0130] (5) Preparation of lithium-ion batteries

[0131] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0132] Example 5

[0133] The battery was prepared and tested according to the following process steps:

[0134] (1) Preparation of positive electrode sheet

[0135] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0136] (2) Preparation of negative electrode sheet

[0137] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0138] (3) Preparation of electrolyte

[0139] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0140] (4) Preparation of isolation membrane

[0141] A polyethylene film is selected as the separating film.

[0142] (5) Preparation of lithium-ion batteries

[0143] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0144] Example 6

[0145] The battery was prepared and tested according to the following process steps:

[0146] (1) Preparation of positive electrode sheet

[0147] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0148] (2) Preparation of negative electrode sheet

[0149] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0150] (3) Preparation of electrolyte

[0151] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0152] (4) Preparation of isolation membrane

[0153] A polyethylene film is selected as the separating film.

[0154] (5) Preparation of lithium-ion batteries

[0155] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0156] Example 7

[0157] The battery was prepared and tested according to the following process steps:

[0158] (1) Preparation of positive electrode sheet

[0159] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0160] (2) Preparation of negative electrode sheet

[0161] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0162] (3) Preparation of electrolyte

[0163] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0164] (4) Preparation of isolation membrane

[0165] A polyethylene film is selected as the separating film.

[0166] (5) Preparation of lithium-ion batteries

[0167] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0168] Example 8

[0169] The battery was prepared and tested according to the following process steps:

[0170] (1) Preparation of positive electrode sheet

[0171] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0172] (2) Preparation of negative electrode sheet

[0173] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0174] (3) Preparation of electrolyte

[0175] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0176] (4) Preparation of isolation membrane

[0177] A polyethylene film is selected as the separating film.

[0178] (5) Preparation of lithium-ion batteries

[0179] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0180] Example 9

[0181] The battery was prepared and tested according to the following process steps:

[0182] (1) Preparation of positive electrode sheet

[0183] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0184] (2) Preparation of negative electrode sheet

[0185] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0186] (3) Preparation of electrolyte

[0187] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0188] (4) Preparation of isolation membrane

[0189] A polyethylene film is selected as the separating film.

[0190] (5) Preparation of lithium-ion batteries

[0191] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0192] Example 10

[0193] The battery was prepared and tested according to the following process steps:

[0194] (1) Preparation of positive electrode sheet

[0195] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0196] (2) Preparation of negative electrode sheet

[0197] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0198] (3) Preparation of electrolyte

[0199] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0200] (4) Preparation of isolation membrane

[0201] A polyethylene film is selected as the separating film.

[0202] (5) Preparation of lithium-ion batteries

[0203] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0204] Embodiment 11

[0205] The battery was prepared and tested according to the following process steps:

[0206] (1) Preparation of positive electrode sheet

[0207] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0208] (2) Preparation of negative electrode sheet

[0209] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0210] (3) Preparation of electrolyte

[0211] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0212] (4) Preparation of isolation membrane

[0213] A polyethylene film is selected as the separating film.

[0214] (5) Preparation of lithium-ion batteries

[0215] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0216] Example 12

[0217] The battery was prepared and tested according to the following process steps:

[0218] (1) Preparation of positive electrode sheet

[0219] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.84:0.16, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0220] (2) Preparation of negative electrode sheet

[0221] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0222] (3) Preparation of electrolyte

[0223] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0224] (4) Preparation of isolation membrane

[0225] A polyethylene film is selected as the separating film.

[0226] (5) Preparation of lithium-ion batteries

[0227] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0228] Example 13

[0229] The battery was prepared and tested according to the following process steps:

[0230] (1) Preparation of positive electrode sheet

[0231] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.04:0.96, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0232] (2) Preparation of negative electrode sheet

[0233] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0234] (3) Preparation of electrolyte

[0235] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0236] (4) Preparation of isolation membrane

[0237] A polyethylene film is selected as the separating film.

[0238] (5) Preparation of lithium-ion batteries

[0239] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0240] Embodiment 14

[0241] The battery was prepared and tested according to the following process steps:

[0242] (1) Preparation of positive electrode sheet

[0243] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.68:0.32, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0244] (2) Preparation of negative electrode sheet

[0245] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0246] (3) Preparation of electrolyte

[0247] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0248] (4) Preparation of isolation membrane

[0249] A polyethylene film is selected as the separating film.

[0250] (5) Preparation of lithium-ion batteries

[0251] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0252] Embodiment 15

[0253] The battery was prepared and tested according to the following process steps:

[0254] (1) Preparation of positive electrode sheet

[0255] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.68:0.32, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0256] (2) Preparation of negative electrode sheet

[0257] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0258] (3) Preparation of electrolyte

[0259] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0260] (4) Preparation of isolation membrane

[0261] A polyethylene film is selected as the separating film.

[0262] (5) Preparation of lithium-ion batteries

[0263] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0264] Example 16

[0265] The battery was prepared and tested according to the following process steps:

[0266] (1) Preparation of positive electrode sheet

[0267] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.68:0.32, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0268] (2) Preparation of negative electrode sheet

[0269] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0270] (3) Preparation of electrolyte

[0271] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. VC, additive b1 and additive b2 are then added and mixed thoroughly.

[0272] (4) Preparation of isolation membrane

[0273] A polyethylene film is selected as the separating film.

[0274] (5) Preparation of lithium-ion batteries

[0275] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0276] Comparative Example 1

[0277] The battery was prepared and tested according to the following process steps:

[0278] (1) Preparation of positive electrode sheet

[0279] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0280] (2) Preparation of negative electrode sheet

[0281] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0282] (3) Preparation of electrolyte

[0283] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L, and then VC is added and mixed thoroughly.

[0284] (4) Preparation of isolation membrane

[0285] A polyethylene film is selected as the separating film.

[0286] (5) Preparation of lithium-ion batteries

[0287] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0288] Comparative Example 2

[0289] The battery was prepared and tested according to the following process steps:

[0290] (1) Preparation of positive electrode sheet

[0291] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0292] (2) Preparation of negative electrode sheet

[0293] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0294] (3) Preparation of electrolyte

[0295] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Additive b1 is then added and mixed thoroughly.

[0296] (4) Preparation of isolation membrane

[0297] A polyethylene film is selected as the separating film.

[0298] (5) Preparation of lithium-ion batteries

[0299] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0300] Comparative Example 3

[0301] The battery was prepared and tested according to the following process steps:

[0302] (1) Preparation of positive electrode sheet

[0303] The positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 98:1.2:0.8, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0304] (2) Preparation of negative electrode sheet

[0305] The negative electrode active material graphite, the conductive agent acetylene black, and the binder SBR are mixed in a mass ratio of 96.5:1.5:2, and deionized water solvent is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0306] (3) Preparation of electrolyte

[0307] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Additive b2 is then added and mixed thoroughly.

[0308] (4) Preparation of isolation membrane

[0309] A polyethylene film is selected as the separating film.

[0310] (5) Preparation of lithium-ion batteries

[0311] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0312] In Examples 1 to 14 and Comparative Examples 1 to 3, b1 and b2 are (I5) ethoxycarbonyl isothiocyanate and (II13) trivinyltrimethylcyclotrisilazane, respectively; in Example 15, b1 and b2 are (I2) and (II3), respectively; in Example 16, b1 and b2 are (I4) and (II9), respectively.

[0313] The performance of the lithium-ion batteries prepared in the examples of the present invention and the comparative examples was tested. See Table 1, which shows the performance test data of the lithium-ion batteries prepared in the examples of the present invention and the comparative examples.

[0314] Table 1

[0315]

[0316] The contents in Table 1 are by mass.

[0317] Among them, the test method of DCR growth rate at 60℃ storage for 60 days is as follows:

[0318] The lithium-ion battery was fixed in capacity, charged to 3.65V at 0.33C constant current, charged to a cut-off current of 0.05C at constant voltage, and discharged to 2.5V at 0.33C, and this was repeated for 3 cycles, with the discharge capacity of the third cycle being taken as the battery capacity. The charge was adjusted to 50% SOC and the DCR was tested: 0.33C was discharged to 50% of the capacity of the third cycle of fixed capacity, and the battery was left to stand for 2 hours, and then 1C was discharged for 18s at 50% SOC, and after standing for 40s, 1C was charged for 10s, and the voltage during the 18s discharge and 10s charging process was recorded to calculate the initial DCR1.

[0319] Then store at 60℃ for 60 days. After the battery temperature drops to room temperature, perform three cycles of constant capacity on the battery under the same conditions as above. Adjust the load to 50% SOC and test DCR: discharge at 0.33C until the capacity is 50% of the third cycle of constant capacity, let stand for 2h, then discharge at 1C for 18s at 50% SOC, let stand for 40s, charge at 1C for 10s, record the voltage during the 18s discharge and 10s charging process, and calculate the DCR2 after storage.

[0320] The battery DCR calculation method is as follows: the voltage at the last second of static state is V0, the voltage after 18s of discharge is V1, the current during discharge is I, and DCR = (V0-V1) / I;

[0321] Calculate DCR growth rate = (DCR2-DCR1) / DCR1 x 100%.

[0322] Battery high temperature cycle performance, that is, the test method of high temperature cycle capacity retention rate:

[0323] The high temperature cycle performance test of the lithium-ion battery was carried out. At a test temperature of 60°C, the lithium-ion battery was allowed to stand for 120 minutes, fully charged at 1C constant current and constant voltage, with a cut-off voltage of 3.65V and a cut-off current of 0.05C, allowed to stand for 20 minutes, and then discharged at 1C constant current to 2.5V; the above was one cycle. The above steps were repeated for a total of 1000 cycles (1000 circles) of charge and discharge, and the discharge capacity of the second circle (Q1) and the discharge capacity of the 1000th circle (Q2) were recorded. The high temperature cycle capacity retention rate = Q2 / Q1×100%.

[0324] From the data in Table 1, combined with Examples 1 to 16 and Comparative Examples 1 to 3, it can be seen that the electrolyte in Examples 1 to 16 contains VC and additive b, no additive b1 is added in Comparative Example 1, and no additive b2 is added in Comparative Example 2. From the energy point of view, when the electrolyte additive b is not added to the electrolyte, the high temperature cycle performance of the battery and the DCR growth rate of 60 days of storage at 60°C are significantly increased.

[0325] In addition, in combination with Examples 1 to 5, it can be seen that when the electrolyte addition amount meets 0.1-3%; and b1 / b2 meets 1-15, and the cohesion and electrolyte additives a and b meet the formula m×(a+b) range 50-600, the battery has better high temperature cycle and lower DCR growth rate.

[0326] In Examples 9 and 10, when the electrolyte addition amount is greater than 0.3% or less than 0.1%, the high temperature cycle performance and battery DCR are slightly worse. In Examples 6 and 7, when the electrolyte additive, the ratio of additive b1 to additive b1 does not meet the range of 1-15, the high temperature cycle performance and battery DCR are slightly worse.

[0327] It can be seen from Examples 12 and 13 that when the cohesion and additives a and b do not satisfy the formula range of 50-600, when the formula is lower than 50, or greater than 600, the high temperature cycle performance and battery DCR of the battery are poor.

[0328] The above is a detailed introduction to a lithium ion battery provided by the present invention and the application of an additive in a lithium ion battery electrolyte in reducing the amount of vinylene carbonate in the electrolyte. The principle and implementation mode of the present invention are described in detail using specific examples herein. The description of the above embodiments is only used to help understand the method and its core idea of ​​the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in the technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in several ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode plate and an electrolyte; The positive electrode plate includes positive electrode active material lithium iron phosphate; The electrolyte includes additive a and additive b; The additive a includes vinylene carbonate; The additive b includes a compound having a structure represented by formula (I) and a compound having a structure represented by formula (II); Wherein, in formula (I), M is selected from fluorinated or non-fluorinated C1-C4 alkyl; In formula (II), R1, R2, and R3 are each independently selected from H or -C n H 2n+1 , where n≤4; R4, R5, and R6 are each independently selected from vinyl, allyl, oxyethylene, or oxyallyl; R7, R8, and R9 are each independently selected from hydrogen, methyl or ethyl.

2. The lithium-ion battery according to claim 1, characterized in that The mass content of the additive b in the electrolyte is 0.1% to 3%; The mass ratio of the compound represented by the structure of formula (I) to the compound represented by the structure of formula (II) is (1-15):

1.

3. The lithium-ion battery according to claim 1, characterized in that The compound of the structure represented by formula (I) includes at least one of the compounds of the structures represented by formulas (I1) to (I17):

4. The lithium-ion battery according to claim 1, characterized in that The compound of the structure represented by formula (II) includes at least one of the compounds of the structures represented by formula (II1) to (II16):

5. The lithium-ion battery according to claim 1, characterized in that: The additive b is specifically ethoxycarbonyl isothiocyanate and trivinyltrimethylcyclotrisilazane.

6. The lithium-ion battery according to claim 1, characterized in that In the electrolyte, the mass content of vinylene carbonate is 0.5% to 2.5%; The mass ratio of the total mass of the compound represented by the structure of formula (I) and the compound represented by the structure of formula (II) to the mass of vinylene carbonate is (0.2-2):

1.

7. The lithium-ion battery according to claim 1, characterized in that: The cohesive force of the positive electrode sheet, vinylene carbonate, the compound of the structure shown in formula (I) and the compound of the structure shown in formula (II) satisfy the following relationship: 50≤m×(a+b)≤600 (1); Wherein, m is the cohesive force of the positive electrode sheet, in N / m; a is the mass percentage of vinylene carbonate in the electrolyte, and b is the sum of the mass percentages of the compound of the structure represented by formula (I) and the compound of the structure represented by formula (II) in the electrolyte.

8. The lithium-ion battery according to claim 7, characterized in that: The cohesive force of the positive electrode sheet satisfies: 20≤m≤200; The mass percentage of the vinylene carbonate in the electrolyte, the mass percentage of the compound with the structure represented by formula (I) and the mass percentage of the compound with the structure represented by formula (II) in the electrolyte satisfy: 0.1≤a+b≤5.

9. The lithium-ion battery according to claim 7, characterized in that: When the cohesive force of the positive electrode sheet is m≤60, b / a≥1.

5.

10. The lithium ion battery according to claim 1, characterized in that: The lithium-ion battery also includes a negative electrode; The negative electrode includes a negative electrode active material; The negative electrode active material includes graphite and / or silicon-based materials.

11. Use of the compound represented by the structure of formula (I) and the compound represented by the structure of formula (II) as an additive in lithium ion battery electrolyte to reduce the amount of vinylene carbonate in the electrolyte; in, In formula (I), M is selected from fluorinated or non-fluorinated C1-C4 alkyl; In formula (II), R1, R2, and R3 are each independently selected from H or -C n H 2n+1 , where n≤4; R4, R5, and R6 are each independently selected from vinyl, allyl, oxyethylene, or oxyallyl; R7, R8, R9 are each independently selected from hydrogen, methyl or ethyl; The lithium ion battery is a lithium iron phosphate lithium ion battery.

12. The use according to claim 11, characterized in that: The application includes the application of the compound having the structure represented by the formula (I) in improving the high temperature performance and / or storage performance of lithium ion batteries; The application includes the application of the compound with the structure represented by formula (II) in improving the high temperature performance and / or storage performance of lithium ion batteries.

Citation Information

Patent Citations

  • Electrolyte for silicon-carbon negative electrode and lithium ion battery

    CN110994022A

  • Silicon-cyanogen electrolyte additive for high-voltage lithium ion battery, electrolyte and battery

    CN111416153A

  • High-voltage low-impedance lithium ion battery electrolyte and lithium ion battery

    CN112397785A

  • Electrolyte and lithium ion battery thereof

    CN115425288A

  • Ternary lithium ion battery electrolyte and lithium ion battery

    CN117013068A

Cited By

  • Lithium ion battery

    CN120319891A

  • A lithium-ion battery

    CN120319891B

  • Lithium battery drying process

    CN120488643A

  • Electrolyte combined additive and high-temperature-resistant lithium ion battery electrolyte

    CN122291697A